The Role of Government Institutions, Social Institutions and Public Spaces in Shaping Community-Based Early Childhood Character Education - khoerudin, koko (Jurnal Pendidikan Raudhatul Athfal, 2024)
The purpose of this study is to examine how the character education bentuk is being implemented in society with a particular emphasis on the function of governmental, social, and public institutions. In this study, we use the qualitative research method with a literature study approach to better understand the role that public spaces, social organizations, and governmental bodies play in character education and how that role affects the development of good character in society. This study explores the perspectives of many stakeholders in the application of character education bentuks in society using data collection approaches from various documentations, including journals and document analysis. It is anticipated that this study's findings will help people better comprehend the significance of the role that governments play in society.